2013
DOI: 10.1093/ageing/aft074
|View full text |Cite
|
Sign up to set email alerts
|

Six-month outcomes following an emergency hospital admission for older adults with co-morbid mental health problems indicate complexity of care needs

Abstract: Background: two-thirds of older patients admitted as an emergency to a general hospital have co-existing mental health problems including delirium, dementia and depression. This study describes the outcomes of older adults with co-morbid mental health problems after an acute hospital admission.Methods: a follow-up study of 250 patients aged over 70 admitted to 1 of 12 wards (geriatric, medical or orthopaedic) of an English acute general hospital with a co-morbid mental health problem and followed up at 180 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 26 publications
2
28
0
1
Order By: Relevance
“…These findings are similar to those in elderly patients with and without delirium in the ED . Interestingly, we found that the median survival of advanced cancer patients with delirium in the ED was only 1.2 months for patients who were CAM‐positive, and these survival outcomes are worse than those of elderly patients with delirium but without cancer in the ED, of whom only 6% died within 1 month in one study and 31%–37% died within 6 months in other studies . Consequently, clinicians caring for advance cancer patients with delirium in EDs should strongly consider focusing on goals of care, resuscitation preferences, and quality of life for patients and their family members.…”
Section: Discussionsupporting
confidence: 80%
“…These findings are similar to those in elderly patients with and without delirium in the ED . Interestingly, we found that the median survival of advanced cancer patients with delirium in the ED was only 1.2 months for patients who were CAM‐positive, and these survival outcomes are worse than those of elderly patients with delirium but without cancer in the ED, of whom only 6% died within 1 month in one study and 31%–37% died within 6 months in other studies . Consequently, clinicians caring for advance cancer patients with delirium in EDs should strongly consider focusing on goals of care, resuscitation preferences, and quality of life for patients and their family members.…”
Section: Discussionsupporting
confidence: 80%
“…These patients are mostly very old (half will be over 85 years old), acutely ill and have many comorbidities 4. Many are reaching the end of their natural life5; there is a palliative element to their care, making the quality of their care and their experience of being in hospital of greater importance. Such patients have many functional problems (incontinence, needing help when moving and assistance with meals) and behavioural and psychological problems (delusions, hallucinations, agitation and aggression and apathy), which together with their acute illness and comorbidities make them especially vulnerable to a poor experience 4.…”
Section: Introductionmentioning
confidence: 99%
“…Older patients with comorbid mental illness also have increased morbidity (Bradshaw et al . ). Furthermore, for patients who have a mental illness, rapid tranquilization, the risk of choking, and the consumption of alcohol and illicit drugs exacerbate risk (Unsworth et al .…”
Section: Introductionmentioning
confidence: 97%
“…In particular, there is good evidence indicating that cardiovascular diseases (hypertension, stroke, myocardial infarction) and nutritional and metabolic diseases (obesity, diabetes, hyperlipidaemia) significantly affect this group (Hert et al 2011) including even young adults (McCloughen et al 2012). Older patients with comorbid mental illness also have increased morbidity (Bradshaw et al 2013). Furthermore, for patients who have a mental illness, rapid tranquilization, the risk of choking, and the consumption of alcohol and illicit drugs exacerbate risk (Unsworth et al 2011) that needs to be managed by staff (Flood et al 2014).…”
Section: Introductionmentioning
confidence: 99%